Experimental Simplified Rule Of Self Tuning Fuzzy Logic-Model Reference Adaptive Speed Controller For Induction Motor Drive - Ismail, Muhamad Zamani; Talib, Md Hairul Nizam; Ibrahim, Zulkifilie; Mat Lazi, Jurifa; Rasin, Zulhani (Institute of Advanced Engineering and Science, 2020)
Fuzzy logic controller (FLC) has shown excellent performance in dealing with the non-linearity and complex dynamic model of the induction motor. However, a conventional constant parameter FLC (CPFL) will not be able to provide-good coverage performance for a wide speed range operation with a single tuning parameter. Therefore, this paper proposed a self tuning mechanism FLC approach by model reference adaptive controller (ST-MRAC) to continuously allow to adjust the parameters. Due to real time hardware application, the dominant rules selection method for simplified rules has been implemented as part of the reducing computational burden. Experiment results validate a good performance of the ST-MRAC compared to the CPFL for the speed performance in terms of the wide range of operations and disturbance showed remarkable performance.